CODESRIA Bulletin Online, No. 4, May 2025 - V. Y. MUDIMBE: A Tribute - Zubairu Wai, (CODESRIA Bulletin, 2025)
When Immanuel Kant died in February 1804, Johann Gottfried Herder, who had attended Kant’s lectures as a youth but who would grow critical of his philosophy in later years, said this about the Prussian philosopher: I have enjoyed the good fortune of knowing a philosopher, who was my teacher … His open brow, built for thought, was the seat of undisturbed contentment and joy; there flowed from his lips a discourse rich in thought; jest and wit and humour were always at his command. … Nothing worth knowing was indifferent to him; no cabal, no sect, no prejudice, no desire for fame, could ever distract him in the slightest from broadening and illuminating the truth. He encouraged and gently impelled others to think for themselves; despotism was foreign to his nature. This man, whom I name with the utmost thankfulness and reverence, is Immanuel Kant. (Gardner 1999: 13) What Herder said about Kant, I say about V. Y. Mudimbe, a philosopher I had the good fortune of knowing and to call my friend. Mudimbe passed away on 21 April 2025 at the age of eighty- three. Once, during a visit to Durham, North Carolina, I asked Mudimbe how he would like to be remembered. Surprised by the question, he responded, ‘But I am just a teacher’. Yet, there was nothing ‘just’ about Mudimbe. He was a pioneering and groundbreaking philosopher, a novelist, a poet and a multidimensional thinker, who advanced our knowledge of African systems of thought and challenged us to develop original new strategies within the social and human disciplines for Africa. His groundbreaking The Invention of Africa (1988), which won the Herskovits Award of the African Studies Association in 1989, reoriented African studies and African philosophy, teaching us new ways of engaging with Africa as an object of knowledge and pushing back against Eurocentric and, frankly, racist representations of the continent. Someone recently remarked that the field of African philosophy, for example, could be broadly divided into two epochs: before and after Mudimbe. This is not an exaggeration. Every major philosophical debate in African philosophy, and indeed every major text in the field since the late 1980s, has been influenced by Mudimbe’s work, especially The Invention of Africa. Born in Jadotville (Likasi), Shaba (Katanga) Province, Belgian Congo (now the Democratic Republic of the Congo), on 8 December 1941, Mudimbe left his family at the tender age of nine for a Catholic seminary conceived ‘to prepare potential candidates for the priesthood’. There, he received an education that he said, ‘basically emphasised Greco-Roman humanism’ and Catholic Christian values. By the time he was eighteen, he had become completely ‘Francophonised’ and ‘subjected to Greco-Roman values and Christian norms’ (his words). Although this would contribute to making him the rigorous and expansive thinker he would become, the seminary experience and its alienating and assimilationist violence dissuaded him from becoming a priest, and despite becoming a Benedictine monk for a brief time in a monastery in Rwanda, it was clear his interests lay elsewhere. He would spend a lifetime trying to make sense of this period of his life as well as seeking to detach himself (unsuccessfully) from its lasting effects. It is the nature and condition of this psycho-existential angst and the quotidian banality of its pathologies that partially fuelled his intellectual work. As he told Boaventura de Sousa Santos, in a conversation at the University of Coimbra, Portugal, in the summer of 2013, for him writing was primarily about coming to terms with the things that made him possible. It was an ekstasis, he said – that is, a way of standing outside of himself and ‘discovering through the very process of reflecting that I am a being-for-others’. This is why his commitment, as he would write in The Invention of Africa, was neither ‘to philosophy, nor to an invented Africa, but to what it essentially means to be an African and a philosopher today’. Mudimbe came of age in the intensely turbulent post-independence political climate that resulted from Congolese independence and the social universe of violence it was built on: the assassination of Patrice Lumumba, Congo’s anticolonial hero; the eventual accession of Mobutu Sese Seko to power; and the civil wars and political violence that would grip the country. Thus, very early on, at the seminary and during the turbulent period of Congolese independence, he witnessed the personal and structural manifestations of a colonising violence and its pathologies of power. Years later, the vagaries of this political and social context would force him into self-imposed exile in the United States, and led him to mourn the victims of violence in Congo, permanently: for more than twenty years Mudimbe would wear only black clothing. Leaving the monastic life at age twenty-one, he studied philosophy at Lovanium University in Kinshasa, before proceeding to France where he earned a Master’s degree in Applied Linguistics at Université de Franche-Comté Besançon in 1966 and in Sociology at the Université de Paris in 1968. In 1970, he completed a doctorate in Philosophy and Letters (with High Honours) at the Université Catholique de Louvain (Leuven, Belgium). Returning to Congo-Zaire in that same year, he quickly rose within the university system, serving in various academic and administrative roles at the newly created National University of Zaire – first in Kinshasa and then Lubumbashi, when the philosophy department was relocated there. However, his dream of building academic institutions that he hoped would serve ‘as sites where thought could illuminate existence’, as Bogumil Jewsiewicki puts it, ended in frustration, as political pressures to conform to the demands of an increasingly authoritarian and repressive regime led him to move to the United States in 1980. On this self-imposed exile, he told Gurav Desai: I chose to leave Zaire in 1980, when Mr Mobutu decided to have me as a member of his Central Committee in charge of, I guess, Ideology and things like that, with I think cabinet status. It seemed sound to me to decline that position because I didn’t think of myself, and I still don’t think of myself, as a politician – my job is to be a teacher, and I have done it resisting all invitations to be involved in politics. In the United States, Mudimbe immediately established himself as the leading African intellectual and one of the twentieth century’s greatest thinkers. He held teaching positions at Haverford College, Stanford University, before finally settling at Duke University, as Newman Ivey White Distinguished Professor of Literature in the Duke Literature Program, until his retirement in 2014. He mentored generations of scholars and shaped debates in postcolonial studies, existentialism, phenomenology, structuralism, African mythical thought and epistemologies. Mudimbe was the recipient of many honours: he was awarded honorary doctorates from Université Paris VII Diderot, the Katholieke Universiteit Leuven, the Université de Lubumbashi (which now houses his library), the Bibliothèque Mudimbe and Laval University in Canada. Mudimbe’s distinctive and erudite critical project defies simple classification: it contributed to various bodies of knowledge, in disciplinary fields such as philosophy, anthropology, theology, postcolonial studies, decolonial theory, literary criticism, cultural studies, prose fiction and African studies more broadly. In his intellectual vocation, his vision was transdisciplinary. Wearing multiple hats, as a philosopher, philologist, anthropologist (even though he rejected this label), historian, novelist and poet, among others, Mudimbe consistently challenged us to rethink the structures within which knowledge is produced about Africa. His scholarship opened numerous vistas into the discursivity of the modern disciplines. Mudimbe was a complex being who defied simple categorisation. In an interview with Gurav Desai in 1991, he described himself as ‘the product of my own time and my space and … my consciousness’. Warning against limiting ourselves to the expectations other place on us, he encouraged us to embrace the complex beings that we are: Sometimes I might introduce myself as a teacher, at other times as an African scholar, or in other circumstances I may be introduced as someone who is interested, let’s say, in phenomenology or the history of ideas. … When we define ourselves, thanks to the expectation we believe that others are having of us, we are limiting, we are simplifying, the complexity of who we are. Mudimbe has been described variously, as polyphonic, a polymath, a multidimensional thinker, a walking bibliothèque or simply someone who ‘read everything’. Toussaint Kafarhire describes him as a critical observer, who lived his human vocation as a testament and a refusal to compromise with banality. To me, personally, he was my teacher, a friend and intellectual father. He was the smartest and most perceptive person I have ever met, a thinker whose erudition and rigour, and the capacious grounds that his thought covered, remain awe-inspiring. It was Mudimbe who taught me how to be an intellectual. But, above all, Mudimbe was a human being whose humility and generosity of spirit were unmatched. His greatest legacy, in addition to his remarkable achievements and the body of work he left on African systems of thought, is the numerous students, such as myself, that he mentored and challenged to think. This will ensure his immortality: V. Y. Mudimbe will never die. Rest well my friend, yours was a life that was well lived. One day, when my own work is done, I hope that I will be able to see you on the other side. Dar es Salaam, Tanzania 2 May 2025